The factors associated with transient hypothyroxinemia of prematurity - Aslan Yilmaz; Yavuz Ozer; Nesrin Kaya; Hande Turan; Hazal Cansu Acar; Oya Ercan; Yildiz Perk; Olcay Evliyaoglu; Mehmet Vural (BMC, 2021)
Abstract Background Hypothyroxinemia is defined by low levels of thyroxine (T4) despite low or normal levels of thyroid-stimulating hormone (TSH). This study aimed to evaluate the factors associated with transient hypothyroxinemia of prematurity (THOP) in newborns admitted to the neonatal intensive care unit (NICU). Method This is a single center, retrospective, case-control study. Premature newborns, between 24 and 34 weeks of gestation, hospitalised between January 2014-December 2019 in Istanbul University-Cerrahpasa Faculty of Medicine NICU were analyzed through their medical records. Thyroid function tests were routinely performed between the 10th and 20th days of postnatal life and were evaluated according to the gestational age references. Thirty six possible associated factors (prenatal and postnatal parameters, medical treatments, clinical diagnoses and applications in NICU) were searched in the patient group with THOP (n = 71) and the control group with euthyroid prematures (n = 73). The factors for THOP were identified by univariate analysis, followed by multivariate analysis. Results Mean gestational ages of the study and the control groups were 29.7 ± 2.48 and 30.5 ± 2.30 weeks, respectively (p = 0.606). The birth weight, small for gestational age (SGA), intraventricular hemorrhage (IVH), congenital heart disease (CHD) were found to be the possible associated factors for THOP in the univariate analysis and CHD (p = 0.007, odds ratio [OR]:4.9, 95% confidence interval [CI]: 1.5-15.8), BW (p = 0.004, OR:0.999, 95% CI: 0.9-1.0) and SGA (p = 0.010, OR:4.6, 95% CI: 1.4-14.7) were found to be factors associated with THOP determined by univariate logistic regression analysis. Conclusıons Although some treatment practices might have had direct effects on pituitary-thyroid axis, related with the severity of the newborn clinical conditions, non of them was found to be a associated factor for THOP. However, CHD and SGA may be considered as associated factors with THOP detected in preterm infants.